Biopsychosocial Model Analysis of a Recurrent Guillain–Barré Syndrome Patient’s Recovery - Prashant P. Naik; Rutuja A. Phadke; Amogh R. Kulkarni; Vishagh K. Nair (Annals of Indian Psychiatry)
Guillain–Barré syndrome (GBS) is an autoimmune disease that generally follows a monophasic course and typically does not recur. This case report explores the application of the biopsychosocial model in the context of a 46-year-old patient who experienced GBS for the second time in 2 years. It highlights the predisposing, precipitating, perpetuating, and protective factors affecting the patient’s biological, psychological, and social aspects during their recovery journey. The patient’s excellent socioeconomic status, social activity, and strong family support along with vigorous physical therapy played a crucial role in their remarkable recovery.